Pickling-like marble and method for making the same

CN116553826BActive Publication Date: 2026-10-27FOSHAN LINGGAO NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310489305.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2026-10-27
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

[0003]虽然硫酸只会在大理石表面进行反应,形成凹凸不平防滑表面,不会与大理石内部发生化学反应,但是酸洗过的大理石表面容易残留硫酸,可能存在腐蚀鞋子或其他物质的隐患,出厂时需要用大量的水冲洗,浪费水资源

Benefits of technology

[0026](1)本发明的仿酸洗大理石,从下到上依次包括坯体层、底釉层、图案层、第一保护釉层、仿酸洗纹路层和第二保护釉层;其中,仿酸洗纹路层所用的釉料包括以下按重量百分计的原料:钾钠长石粉30~35%、纯碱5~6%、碳酸钡15~20%、氧化铝10~12%、白云石4~5%、方解石7~10%、石英粉13~15%和氧化锌5~6%。本发明的仿酸洗大理石无需酸洗,只需要设置特定的仿酸洗纹路层就能形成凹凸不平的防滑纹路,节省了酸液和水资源。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116553826B_ABST
    Figure CN116553826B_ABST
Patent Text Reader

Abstract

The application discloses a kind of imitation pickling marbles and preparation methods thereof, imitation pickling marble includes blank layer, bottom glaze layer, pattern layer, first protective glaze layer, imitation pickling line layer and second protective glaze layer from bottom to top in sequence;Wherein, the glaze used in imitation pickling line layer includes the following raw materials by weight percentage: potassium sodium feldspar powder 30-35%, soda ash 5-6%, barium carbonate 15-20%, alumina 10-12%, dolomite 4-5%, calcite 7-10%, quartz powder 13-15% and zinc oxide 5-6%. The imitation pickling marble of the application does not need pickling, only needs to set specific imitation pickling line layer to form uneven anti-skid line, saves acid and water resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of marble processing, and specifically to an imitation acid-washed marble and its preparation method. Background Technology

[0002] The acid washing process for stone generally refers to the acid washing process for marble. Marble is a crystalline limestone, and its main component is calcium carbonate (CaCO3). The marble acid washing process involves spraying sulfuric acid onto the marble surface. The chemical formula for sulfuric acid is H2SO4. Calcium carbonate reacts with sulfuric acid to produce calcium sulfate, which is a very fine particle that adheres to the calcium carbonate and prevents the calcium carbonate on the surface from reacting with the sulfuric acid again.

[0003] Although sulfuric acid only reacts on the surface of marble, creating an uneven, non-slip surface, and does not chemically react with the marble's interior, acid-washed marble is prone to sulfuric acid residue, which may pose a risk of corroding shoes or other substances. It requires extensive rinsing with water during manufacturing, wasting water resources. Furthermore, it's not recommended to polish acid-washed marble with a grinder because the uneven surface makes polishing difficult and reduces the surface's non-slip properties. The most direct method is to scrub it directly with a brush and dish soap. Summary of the Invention

[0004] To overcome the shortcomings of the prior art, one objective of this invention is to provide an acid-washed marble that, by setting an acid-washed texture layer, can form an acid-washed texture without acid washing, thus saving water resources. Another objective of this invention is to provide a method for preparing acid-washed marble that is simple in steps and suitable for large-scale industrial production.

[0005] One of the objectives of this invention is achieved through the following technical solution:

[0006] An imitation acid-washed marble comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer, a first protective glaze layer, an imitation acid-washed texture layer, and a second protective glaze layer; wherein, the glaze used in the imitation acid-washed texture layer comprises the following raw materials by weight percentage: 30-35% potassium sodium feldspar powder, 5-6% soda ash, 15-20% barium carbonate, 10-12% alumina, 4-5% dolomite, 7-10% calcite, 13-15% quartz powder, and 5-6% zinc oxide.

[0007] Furthermore, the raw materials used in the blank layer include the following components by weight percentage: 45-50% water-milled abrasive, 4-6% diopside, 2-5% talc powder, 1-3% calcined talc, 7-9% potassium sodium stone powder, 2-3% bentonite, 20-30% black clay, and 5-10% ball clay.

[0008] Furthermore, the glaze used in the base glaze layer comprises the following raw materials by weight percentage: 50-55% feldspar, 12-20% nepheline powder, 4-6% quartz powder, 7-10% kaolin, 2-6% dolomite, 5-10% talc, 5-7% alumina, and 2-5% siliceous shale.

[0009] Furthermore, the glaze used in the first protective glaze layer comprises the following raw materials by weight percentage: feldspar 45-55%, kaolin 5-10%, dolomite 7-12%, talc 2-4%, quartz powder 6-12%, zinc oxide 4-6%, barium carbonate 4-6%, siliceous shale 2-5%, and calcite 4-6%.

[0010] Furthermore, the glaze used in the second protective glaze layer comprises the following raw materials by weight percentage: feldspar 45-55%, kaolin 5-10%, dolomite 7-12%, talc 2-4%, quartz powder 6-12%, zinc oxide 4-6%, barium carbonate 4-6%, siliceous shale 2-5%, and calcite 4-6%.

[0011] The second objective of this invention is achieved by the following technical solution:

[0012] The above-mentioned method for preparing imitation acid-washed marble includes the following steps: body layer, base glaze layer, pattern layer, first protective glaze layer, imitation acid-washed texture layer, and second protective glaze layer.

[0013] 1) Prepare the glaze materials for the base glaze layer, the first protective glaze layer, the imitation acid pickling texture layer, and the second protective glaze layer to obtain the base glaze, the first protective glaze, the imitation acid pickling texture glaze, and the second protective glaze, respectively.

[0014] 2) Mix the raw materials for the billet, press them, and dry them to obtain the bottom layer of the billet;

[0015] 3) Apply a base glaze to the bottom of the clay body to form a base glaze layer;

[0016] 4) Inkjet printing of patterns onto the base glaze layer to form a pattern layer;

[0017] 5) Apply the first protective glaze to the pattern layer to form the first protective glaze layer;

[0018] 6) Apply an acid-wash textured glaze to the first protective glaze layer to form an acid-wash textured layer;

[0019] 7) Apply a second protective glaze to the imitation acid-washed texture layer to form a second protective glaze layer, thus obtaining a semi-finished product;

[0020] 8) The semi-finished product obtained in step 7) is fired and shaped, and then polished to obtain imitation acid-washed marble.

[0021] Further, in step 1), the preparation method of the imitation acid-washed textured glaze includes the following steps: first, the glaze material used for the imitation acid-washed textured layer includes small-particle dry granules and large-particle dry granules; the small-particle dry granules and large-particle dry granules are mixed, calcined, and then dried to obtain a frit glaze; then, liquid is added and mixed evenly to obtain the imitation acid-washed textured glaze; wherein, the particle size of the small-particle dry granules is 0.2 to 0.5 times that of the large-particle dry granules. Preferably, the small-particle dry granules account for 20 to 40% of the total raw material mass, and the large-particle dry granules account for 60 to 80% of the total raw material mass. More preferably, the small-particle dry granules account for 20% of the total raw material mass, and the large-particle dry granules account for 80% of the total raw material mass. The size of the small-particle dry granules is 8 to 20 mesh, and the size of the large-particle dry granules is 20 to 40 mesh. The initial melting point of both is 800 to 850°C, preferably 850°C.

[0022] Furthermore, the calcination temperature is 1500–2000℃, and the calcination time is 10–20 min; the frit glaze is crushed to a particle size of 20–60 mesh, and then liquid is added and mixed to obtain an acid-washed textured glaze.

[0023] Furthermore, in step 2), the drying temperature is 150–200°C and the time is 30–60 min.

[0024] Furthermore, in step 8), the firing and shaping process is as follows: first, preheat the temperature to 500-600℃, then heat the temperature to 1100-1200℃ for 15-20 minutes, and finally cool the temperature to 500-600℃ for cooling. The total firing and shaping time is 50-55 minutes.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0026] (1) The imitation acid-washed marble of the present invention comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer, a first protective glaze layer, an imitation acid-washed texture layer, and a second protective glaze layer; wherein, the glaze used in the imitation acid-washed texture layer comprises the following raw materials by weight percentage: 30-35% potassium sodium feldspar powder, 5-6% soda ash, 15-20% barium carbonate, 10-12% alumina, 4-5% dolomite, 7-10% calcite, 13-15% quartz powder, and 5-6% zinc oxide. The imitation acid-washed marble of the present invention does not require acid washing; only a specific imitation acid-washed texture layer is needed to form an uneven, non-slip texture, saving acid and water resources.

[0027] (2) The base glaze layer of the imitation acid-washed marble of the present invention can cover the bottom of the blank, suppress air bubbles, make the bottom of the blank flat, and ensure the inkjet effect of the subsequent pattern layer. The first protective glaze layer can further suppress the air bubbles on the bottom of the blank, play the role of color development and fix the next layer. The second protective glaze layer can play the role of fixing the imitation acid-washed texture layer, and can also increase the luster and touch.

[0028] (3) In the preparation method of the imitation acid-washed marble of the present invention, the imitation acid-washed texture layer uses matte particles of different sizes with different fineness, and the gloss and texture resemble stone that has been aged for a certain period of time. By controlling the initial melting point and firing temperature, the small dry particles are completely melted, while the large dry particles are not completely melted. After being taken out of the kiln, they are polished. The unmelted raised parts are partially polished to form a smooth surface, while the completely melted recessed parts cannot be polished, thus forming a stacked effect, which is very similar to the effect of acid-washed stone. In order to prevent the surface layer from drying out, a layer of transparent glaze is also applied under the dry particles. However, the acid-washed marble cannot be ground and polished, so its gloss is significantly lower than that of the imitation acid-washed marble of the present invention. Attached Figure Description

[0029] Figure 1 This is a photograph of the simulated acid-washed marble from Example 1.

[0030] Figure 2 This is a photograph of the actual marble used in Comparative Example 1;

[0031] Figure 3 This is a picture of commercially available acid-washed marble. Detailed Implementation

[0032] The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0033] Example 1

[0034] An imitation acid-washed marble comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer, a first protective glaze layer, an imitation acid-washed texture layer, and a second protective glaze layer; wherein, the glaze used in the imitation acid-washed texture layer comprises the following raw materials by weight percentage: 34% potassium sodium feldspar powder, 5.8% soda ash, 18% barium carbonate, 10.8% alumina, 4.5% dolomite, 8% calcite, 13.4% quartz powder, and 5.5% zinc oxide.

[0035] The raw materials used in the green body layer include the following components by weight percentage: 46.5% water-milled material, 5% diopside, 3% talc powder, 2% calcined talc, 8% potassium sodium stone powder, 2.5% bentonite, 25% black clay, and 8% ball clay. The preparation method of the raw materials used in the green body layer is as follows: after mixing the raw materials, water is added and the mixture is ball-milled in a grinding mill. The parameters of the resulting raw materials are: slurry flow rate cup test data 50s, specific gravity cup data 1.51, specific gravity cup slurry fineness 250 mesh sieve, sieve residue 1.1g, and then spray-dried.

[0036] The glaze used in the base glaze layer comprises the following raw materials by weight percentage: feldspar 51%, nepheline powder 15%, quartz powder 5%, kaolin 8%, dolomite 5%, talc 6%, alumina 6%, and siliceous shale 4%.

[0037] The first protective glaze layer comprises the following raw materials by weight percentage: feldspar 50%, kaolin 8%, dolomite 10%, talc 3%, quartz powder 10%, zinc chloride 5%, barium carbonate 5%, siliceous shale 4%, and calcite 5%. The second protective glaze layer comprises the same glaze as the first protective glaze layer. The preparation method of the first and second protective glazes includes the following steps: mixing the raw materials, adding water and ball milling in a grinding mill, and obtaining the following parameters for the glaze: slurry flow rate cup test data 75s, specific gravity cup data 1.90, specific gravity cup slurry fineness passing through a 320-mesh sieve, and sieve residue 0.7g.

[0038] The above-mentioned method for preparing imitation acid-washed marble includes the following steps: body layer, base glaze layer, pattern layer, first protective glaze layer, imitation acid-washed texture layer, and second protective glaze layer.

[0039] 1) Prepare the glazes for each layer to obtain the base glaze, the first protective glaze, the imitation acid-washed texture glaze, and the second protective glaze;

[0040] 2) Mix the raw materials of the billet, add water to the grinding mill for ball milling, press it with a press at a pressure of 15000kN, and dry it in a drying kiln at 180℃ for 40min to obtain the bottom layer of the billet;

[0041] 3) Apply a base glaze to the bottom of the blank to form a base glaze layer; the standard glaze application amount is 90g per 300*600mm area.

[0042] 4) Inkjet printing of patterns onto the base glaze layer to form a pattern layer;

[0043] 5) Apply the first protective glaze to the pattern layer to form the first protective glaze layer; standard glaze application: 32g of material per 300*600mm;

[0044] 6) Apply an acid-wash textured glaze onto the first protective glaze layer using a cloth-laying machine to form an acid-wash textured layer; Standard usage: 185g of material per 300*600mm, thickness 1.2mm;

[0045] 7) Apply a second protective glaze to the imitation acid-washed texture layer to form a second protective glaze layer, thus obtaining a semi-finished product;

[0046] 8) The semi-finished product obtained in step 7) is fired and shaped, then polished to obtain the following: Figure 1The simulated acid-washed marble shown is shown. The firing and shaping steps are as follows: first, preheat the temperature to 550℃, then heat it to 1150℃ for 16 minutes, and finally cool it down to 550℃. The total firing and shaping time is 50 minutes.

[0047] In step 1), the preparation method of the imitation acid-washed textured glaze includes the following steps: the glaze used for the imitation acid-washed textured layer comprises 20wt% small dry particles and 80wt% large dry particles. The small and large dry particles are mixed, calcined, and then dried to obtain a frit glaze. Liquid is then added and mixed to obtain the imitation acid-washed textured glaze. The particle size of the small dry particles is 0.2–0.5 times that of the large dry particles. Preferably, the size of the small dry particles is 10 mesh, and the size of the large dry particles is 30 mesh. The initial melting point of both is 850℃.

[0048] Example 2

[0049] An imitation acid-washed marble comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer, a first protective glaze layer, an imitation acid-washed texture layer, and a second protective glaze layer; wherein, the glaze used in the imitation acid-washed texture layer comprises the following raw materials by weight percentage: 35% potassium sodium feldspar powder, 6% soda ash, 20% barium carbonate, 10% alumina, 4% dolomite, 7% calcite, 13% quartz powder, and 5% zinc oxide.

[0050] The raw materials used in the green body layer include the following components by weight percentage: 50% water-milled material, 4% diopside, 5% talc powder, 2% calcined talc, 9% potassium sodium stone powder, 2% bentonite, 23% black clay, and 5% ball clay. The preparation method of the raw materials used in the green body layer is as follows: after mixing the raw materials, water is added and the mixture is ball-milled in a grinding mill. The parameters of the resulting raw materials are: slurry flow rate cup test data 40s, specific gravity cup data 1.50, specific gravity cup slurry fineness 250 mesh sieve, sieve residue 1.0g, and then spray-dried.

[0051] The glaze used in the base glaze layer comprises the following raw materials by weight percentage: feldspar 55%, nepheline powder 20%, quartz powder 4%, kaolin 7%, dolomite 2%, talc 5%, alumina 5%, and siliceous shale 2%.

[0052] The first protective glaze layer uses the following raw materials by weight percentage: feldspar 49%, kaolin 5%, dolomite 12%, talc 4%, quartz powder 12%, zinc chloride 4%, barium carbonate 4%, siliceous shale 4%, and calcite 6%. The second protective glaze layer uses the same glaze as the first protective glaze layer. The preparation method of the first and second protective glazes includes the following steps: mixing the raw materials, adding water and ball milling in a grinding mill, and obtaining the following parameters for the glaze: slurry flow rate cup test data 60ss, specific gravity cup data 1.88, specific gravity cup slurry fineness 320 mesh sieve, sieve residue 0.6g.

[0053] The above-mentioned method for preparing imitation acid-washed marble includes the following steps: body layer, base glaze layer, pattern layer, first protective glaze layer, imitation acid-washed texture layer, and second protective glaze layer.

[0054] 1) Prepare the glazes for each layer to obtain the base glaze, the first protective glaze, the imitation acid-washed texture glaze, and the second protective glaze;

[0055] 2) Mix the raw materials of the billet, add water to the grinding mill for ball milling, press it with a press at a pressure of 14000kN, and dry it in a drying kiln at 150℃ for 60min to obtain the bottom layer of the billet;

[0056] 3) Spray a base glaze onto the bottom layer of the blank to form a base glaze layer; the thickness of the glaze is 0.2mm;

[0057] 4) Inkjet printing of patterns onto the base glaze layer to form a pattern layer;

[0058] 5) Spray the first protective glaze onto the pattern layer to form the first protective glaze layer; the thickness of the glaze is 0.11 mm;

[0059] 6) Apply an acid-wash textured glaze onto the first protective glaze layer using a cloth-laying machine to form an acid-wash textured layer; Standard usage: 180g of material per 300*600mm, thickness 1mm;

[0060] 7) Apply a second protective glaze to the imitation acid-washed texture layer to form a second protective glaze layer, thus obtaining a semi-finished product;

[0061] 8) The semi-finished product obtained in step 7) is fired and shaped, then polished to obtain the following: Figure 1 The example shown is an imitation acid-washed marble. The firing and shaping process involves: first, preheating to 500℃, then firing at 1100℃ for 20 minutes, and finally cooling to 500℃ for a total firing and shaping time of 50 minutes.

[0062] In step 1), the preparation method of the imitation acid-washed textured glaze includes the following steps: the glaze used for the imitation acid-washed textured layer comprises 30wt% small dry particles and 70wt% large dry particles. The small and large dry particles are mixed, calcined, and then dried to obtain a frit glaze. Liquid is then added and mixed to obtain the imitation acid-washed textured glaze. The size of the small dry particles is 8 mesh, and the size of the large dry particles is 20 mesh. The initial melting point of both is 800℃.

[0063] Example 3

[0064] An imitation acid-washed marble comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer, a first protective glaze layer, an imitation acid-washed texture layer, and a second protective glaze layer; wherein, the glaze used in the imitation acid-washed texture layer comprises the following raw materials by weight percentage: 30% potassium sodium feldspar powder, 5% soda ash, 17% barium carbonate, 12% alumina, 5% dolomite, 10% calcite, 15% quartz powder, and 6% zinc oxide.

[0065] The raw materials used in the green body layer include the following components by weight percentage: 45% water-milled material, 4% diopside, 5% talc powder, 3% calcined talc, 7% potassium sodium stone powder, 2% bentonite, 24% black clay, and 10% ball clay. The preparation method of the raw materials used in the green body layer is as follows: after mixing the raw materials, water is added and the mixture is ball-milled in a grinding mill. The parameters of the resulting raw materials are: slurry flow rate cup test data 60s, specific gravity cup data 1.55, specific gravity cup slurry fineness 250 mesh sieve, sieve residue 1.2g, and then spray-dried.

[0066] The glaze used in the base glaze layer comprises the following raw materials by weight percentage: feldspar 55%, nepheline powder 12%, quartz powder 4%, kaolin 8%, dolomite 6%, talc 8%, alumina 5%, and siliceous shale 2%.

[0067] The first protective glaze layer comprises the following raw materials by weight percentage: feldspar 55%, kaolin 8%, dolomite 7%, talc 4%, quartz powder 12%, zinc chloride 4%, barium carbonate 4%, siliceous shale 2%, and calcite 4%. The second protective glaze layer comprises the following raw materials by weight percentage: feldspar 50%, kaolin 10%, dolomite 7%, talc 6%, quartz powder 10%, zinc chloride 4%, barium carbonate 4%, siliceous shale 4%, and calcite 5%.

[0068] The preparation method of the first protective glaze and the second protective glaze includes the following steps: mixing the raw materials, adding water in a grinding mill for ball milling, and obtaining the glaze parameters as follows: slurry flow rate cup test data 90s, specific gravity cup data 1.92, specific gravity cup slurry fineness 325 mesh sieve, sieve residue 0.8g.

[0069] The above-mentioned method for preparing imitation acid-washed marble includes the following steps: body layer, base glaze layer, pattern layer, first protective glaze layer, imitation acid-washed texture layer, and second protective glaze layer.

[0070] 1) Prepare the glazes for each layer to obtain the base glaze, the first protective glaze, the imitation acid-washed texture glaze, and the second protective glaze;

[0071] 2) Mix the raw materials of the billet, add water to the grinding mill for ball milling, press it with a press at a pressure of 16800kN, and dry it in a drying kiln at 200℃ for 30 minutes to obtain the bottom layer of the billet;

[0072] 3) Apply a base glaze to the bottom of the blank to form a base glaze layer; standard glaze application: 92g of material per 300*600mm area;

[0073] 4) Inkjet printing of patterns onto the base glaze layer to form a pattern layer;

[0074] 5) Apply the first protective glaze to the pattern layer to form the first protective glaze layer; standard glaze application amount: 34g of material per 300*600mm;

[0075] 6) Apply an acid-wash textured glaze onto the first protective glaze layer using a cloth-laying machine to form an acid-wash textured layer; Standard usage: 190g of material per 300*600mm, thickness 1.5mm;

[0076] 7) Apply a second protective glaze to the imitation acid-washed texture layer to form a second protective glaze layer, thus obtaining a semi-finished product;

[0077] 8) The semi-finished product obtained in step 7) is fired and shaped, then polished to obtain the following: Figure 1 The simulated acid-washed marble shown is produced by firing and shaping the following steps: first, preheating to 600℃, then firing at 1200℃ for 15 minutes, and finally cooling to 600℃. The total firing and shaping time is 55 minutes.

[0078] In step 1), the preparation method of the imitation acid-washed textured glaze includes the following steps: the glaze used for the imitation acid-washed textured layer comprises 40wt% small dry particles and 60wt% large dry particles. The small and large dry particles are mixed, calcined, and then dried to obtain a frit glaze. Liquid is then added and mixed to obtain the imitation acid-washed textured glaze. The small dry particles have a size of 20 mesh, and the large dry particles have a size of 40 mesh. The initial melting point of both is 830℃.

[0079] Comparative Example 1

[0080] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not have an acid-wash textured layer, resulting in the following: Figure 2 The marble shown. The remaining layers are the same as in Example 1.

[0081] Comparative Example 2

[0082] Comparative Example 2 is acid-washed marble purchased from Guangdong Wangfu Guoshi Building Materials Co., Ltd.

[0083] Performance testing

[0084] I. Texture Effect

[0085] Depend on Figures 1-3It can be seen that the imitation acid-washed marble of Example 1 has raised three-dimensional textures, similar to those of the acid-washed marble of Comparative Example 2. This indicates that the imitation acid-washed marble of the present invention can achieve the antique texture effect of acid washing without acid washing. However, Comparative Example 1 does not have raised three-dimensional textures, indicating that the imitation acid-washed texture layer is the main technical means to achieve the raised texture.

[0086] II. Hardness Test

[0087] Testers conducted Mohs hardness tests on Examples 1-3 and Comparative Examples 1-2, respectively. The specific testing method was as follows: 10 ceramic tiles of known Mohs hardness were selected for each group. The standards were: talc (Level 1), gypsum (Level 2), calcite (Level 3), fluorite (Level 4), apatite (Level 5), feldspar (Level 6), quartz (Level 7), topaz (Level 8), corundum (Level 9), and diamond (Level 10). The level of hardness that caused the damage to the glaze of each tile was observed, and the hardness was expressed as the measured scratch depth. Specific data are shown in Table 1.

[0088] Table 1. Mohs hardness data for each group

[0089] Example 1 7 Example 2 6 Example 3 7 Comparative Example 1 4 Comparative Example 2 5

[0090] As shown in Table 1, the ceramic tiles of Examples 1 to 3 have a Mohs hardness of up to 7, which is higher than that of acid-washed marble sold on the market, and their anti-slip properties are also greatly improved.

[0091] III. Abrasion Resistance Test

[0092] Testers conducted abrasion resistance tests on Examples 1-3 and Comparative Examples 1-2, respectively. The abrasion resistance test of ceramic tiles was mainly conducted according to the "Test Methods for Ceramic Tiles Part VII" (GB / T3810.7—2016). The principle is as follows: the abrasion resistance of ceramic tiles is tested by placing and rotating an abrasive medium on the glazed surface, comparing and contrasting the abraded ceramic tile samples with unaffected samples, and evaluating the abrasion resistance of the marble. The abrasion resistance grading standards for the products are shown in Table 2. The abrasion resistance grading data for each group of products are shown in Table 3.

[0093] Table 2 Marble Abrasion Resistance Grading

[0094]

[0095] Table 3. Abrasion resistance data for each group of marble products

[0096] Example 1 4 Example 2 3 Example 3 3 Comparative Example 1 2 Comparative Example 2 3

[0097] As shown in Table 3, the abrasion resistance level of the acid-washed marble sold in Comparative Example 2 all reached level 3, meeting the requirements for marble leaving the factory. However, the abrasion resistance level of the ceramic tile products in Examples 1-3 reached as high as level 4, which is higher than that of Comparative Examples 1-2, indicating that the ceramic tile products of the present invention have a superior anti-abrasion effect.

[0098] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.

Claims

1. A type of imitation acid-washed marble, characterized in that, From bottom to top, the layers consist of a body layer, a base glaze layer, a pattern layer, a first protective glaze layer, an imitation acid-washed texture layer, and a second protective glaze layer. The glaze used in the imitation acid-washed texture layer comprises the following raw materials by weight percentage: 30-35% potassium sodium feldspar powder, 5-6% soda ash, 15-20% barium carbonate, 10-12% alumina, 4-5% dolomite, 7-10% calcite, 13-15% quartz powder, and 5-6% zinc oxide. The glaze used in the first protective glaze layer includes the following raw materials by weight percentage: feldspar 45-55%, kaolin 5-10%, dolomite 7-12%, talc 2-4%, quartz powder 6-12%, zinc oxide 4-6%, barium carbonate 4-6%, siliceous shale 2-5%, and calcite 4-6%. The glaze used in the second protective glaze layer includes the following raw materials by weight percentage: feldspar 45-55%, kaolin 5-10%, dolomite 7-12%, talc 2-4%, quartz powder 6-12%, zinc oxide 4-6%, barium carbonate 4-6%, siliceous shale 2-5%, and calcite 4-6%. The preparation method of imitation acid-washed marble includes the following steps: 1) Prepare glaze materials for a base glaze layer, a first protective glaze layer, an imitation acid-washed texture layer, and a second protective glaze layer, respectively obtaining the base glaze, the first protective glaze, the imitation acid-washed texture glaze, and the second protective glaze; wherein, the preparation method of the imitation acid-washed texture glaze includes the following steps: first, the glaze material used for the imitation acid-washed texture layer includes small dry particles and large dry particles; mix the small dry particles and large dry particles, calcine them, and then dry them to obtain a frit glaze; crush the frit glaze to a particle size of 20-60 mesh, and then add liquid to mix evenly to obtain the imitation acid-washed texture glaze; wherein, the particle size of the small dry particles is 0.2-0.5 times that of the large dry particles, and the initial melting point of both is 800-850℃; the calcination temperature is 1500-2000℃, and the calcination time is 10-20 min; 2) Mix the raw materials for the green body, press them, and dry them to obtain the green body layer; 3) Apply a base glaze to the body layer to form a base glaze layer; 4) Inkjet printing of patterns onto the base glaze layer to form a pattern layer; 5) Apply the first protective glaze to the pattern layer to form the first protective glaze layer; 6) Apply an acid-wash textured glaze to the first protective glaze layer to form an acid-wash textured layer; 7) Apply a second protective glaze to the imitation acid-washed texture layer to form a second protective glaze layer, thus obtaining a semi-finished product; 8) The semi-finished product obtained in step 7) is fired and shaped, and then polished to obtain imitation acid-washed marble.

2. The imitation acid-washed marble as described in claim 1, characterized in that, The raw materials used in the blank layer include the following components by weight percentage: 45-50% water-milled abrasive, 4-6% diopside, 1-3% calcined talc, 7-9% potassium sodium stone powder, 2-3% bentonite, 20-30% black clay, and 5-10% ball clay.

3. The imitation acid-washed marble as described in claim 1, characterized in that, The glaze used in the base glaze layer comprises the following raw materials by weight percentage: 50-55% feldspar, 12-20% nepheline powder, 4-6% quartz powder, 7-10% kaolin, 2-6% dolomite, 5-10% talc, 5-7% alumina, and 2-5% siliceous shale.

4. The imitation acid-washed marble as described in claim 1, characterized in that, In step 2) of the preparation of the imitation acid-washed marble, the drying temperature is 150-200℃ and the time is 30-60min.

5. The imitation acid-washed marble as described in claim 1, characterized in that, In step 8) of the preparation of the imitation acid-washed marble, the firing and shaping step is as follows: first, the temperature is raised to 500-600℃ for preheating, then the temperature is raised to 1100-1200℃ for firing for 15-20 minutes, and finally the temperature is lowered to 500-600℃ for cooling. The total firing and shaping time is 50-55 minutes.

Citation Information

Patent Citations

  • Rock plate and preparation method thereof

    CN113845357A